Critical Study of Islamic Educational Language in the Naquib Al – Attas Perspective - Nasiri, Nasiri; Afifah, Afifah (International Journal of Islamic Thought and Humanities, 2024)
Linguistically, Islamic education has the equivalent of Arabic words in the form of tarbiyah, ta'lim, and ta'dib. After reviewing the meanings of the three languages, each of them has a characteristic that has consequences on different target fields. Tarbiyah is more directed to the physical- material aspect; ta'lim leads more to cognitive-intellectual aspects ; ta'dib is more directed towards moral-spiritual aspects. In the study of Naquib al-Attas, in fact the Arabic language which is more appropriate to be used as the equivalent of Islamic education is ta'dib, because ta'dib contains words that focus on the formation of a moral-affective domain, where it is the essence of the goals of Islamic education. However, the study of al-Attas was not automatically agreed upon by other Muslim scientists. Many of them are pro, but not a few contra. Ijtihad al-Attas about ta'dib, although it produced a monumental finding, tarbiyah is still popularly applied in pointing out the language of Islamic education.